Serendipitous Discovery of a Prodrug of a PARP‐1 Inhibitor. (22nd August 2013) - Dunn, Derek; Husten, Jean; Aimone, Lisa D.; Ator, Mark A.; Chatterjee, Sankar
Abstract : During SAR development of previously reported pyrrolocarbazole1, a potent PARP‐1 inhibitor, compound14, was discovered serendipitously to be a prodrug of compound1 . Abstract : Compound14 behaves as a water‐soluble prodrug of pyrrolocarbazole1, a potent PARP‐1 inhibitor.